Clinical and Epidemiological Factors Associated with Clostridioides difficile Infection in a Tertiary Hospital in Medellín, Colombia - Ortiz-Marín, Diana Cristina; Montaño-Mejía, Juliana; Cardona-Arango, María Dorys; López-Estrada, Carolina; Villa-Franco, Juan Pablo; Cardeño-Sánchez, John Jairo; Restrepo-Castro, Carlos Andrés (Iatreia, 2024)
Introduction: Clostridioides difficile is the most common cause of health-care-associated diarrhea in adults. In Medellín, infections by this microorganism are frequent in high-complexity hospitals. Objectives: To identify the clinical and epidemiological factors associated with C. difficile infection in a high-complexity university hospital in Medellín, Colombia. Methods: A retrospective cross-sectional epidemiological study was conducted to determine the prevalence and assess potential factors associated with C. difficile infection. A total of 156 patients hospitalized in a high-complexity hospital in Medellín between 2016–2018, who exhibited loose stools with clinical criteria for infection and underwent a toxin test for C. difficile (Immunocard®) with a positive result, were included. Results: A general prevalence of 50% was observed, with a mortality attributable to C. difficile infection of 11.5%. Prevalence ratio (PRa) analysis revealed that factors increasing the likelihood of infection included urban origin (PRa = 3.39; 95% CI: 1.03–11.15), receiving antibiotics for more than 22 days (PRa = 1.81; 95% CI: 1.11–2.95), history of diabetes (PRa = 1.65; 95% CI: 1.16–2.35), solid neoplasia (PRa = 1.64; 95% CI: 1.11–2.41), and previous hospitalization at the institution (PRa = 1.58; 95% CI: 1.13–2.21). Conclusions: This study highlighted associations with C. difficile infection from factors similar to those described in the literature, such as comorbidities, exposure to antibiotics, and hospital care.